20th century regulation of private property in the United States: Disasters, institutional evolution, and social conflict. (January 2020) - Jacobs, Harvey M.
Abstract: The U.S. is known as a nation founded on and committed to the institution of private property. For the first 125 years of its history there was limited regulatory-based social management of private property. Beginning in the early 20th century there began a century-long process of change. This change was characterized by increasing amounts of public regulation at the local, state and national levels. These changes were often prompted by one or more types of disasters (significant social, economic, and ecological disruptions). Always these changes were socially contentious but the social contention became particularly acrimonious in the late 20th century. This paper examines the interactions among disasters, public regulation of private property and social conflict over this regulation throughout the 20th century in the United States. It concentrates on explaining why, even though social conflict has always been present when regulation has been proposed or newly implemented, social conflict became a dominant component of social and policy discourse in the late 20th century.